Batman, the Dark Knight returns - Miller, Frank 1957- (DC Comics, 2017)
Celebrate 30 years of one of the most influential stories ever told in the comics medium with the anniversary edition of the undisputed graphic novel masterpiece BATMAN: THE DARK KNIGHT RETURNS.
Keywords: Superhero comic books, strips, etc; COMICS & GRAPHIC NOVELS / Superheroes; Superheroes; Comic books, strips, etc; Graphic novels; Comic